MULTIDIMENSIONAL CHALLENGES OF THE URBAN POOR IN ACHIEVING THE INDIVIDUAL ECONOMIC SUSTAINABILITY - Ramli, Mohamad Faizal; Senin, Aslan Amat; Majid, Muhammad (Veredas do Direito, 2026)
The problems caused by urban poverty are growing in severity in Malaysia as its cities expand. This study analyses the difficulties faced by the urban poor in attaining their own economic sustainability. Semi-structured interviews were conducted with eight participants, comprising seven urban poor community members and one community leader. The findings show three main challenges: an increasing cost of living, limited employment and job insecurity, and crime and social problems. Legislation, healthcare, and education have increased in cost, which has a direct impact on people’s available income. Furthermore, the informal sector reduces community income and mobility, and the social issues of drug abuse and theft increase crime at the community level. The challenges show the complexity and interwoven problems of urban poverty and the individual’s economic self-sufficiency. The study adds to the existing literature by documenting the empirical findings from the context of urban poverty in Malaysia and adds to the list of advocacies by international organisations, such as the United Nations, on the need for integrated policy redesign for urban poverty in conjunction with the Sustainable Development Goals: Impacting Income, Sustaining Assistance and Services, and Urban Development.